Assessment of Functional Outcome of Intertrochanteric Fractures Treated by PFN A2 in Elderly Patients in a Tertiary Care Hospital - Thimmaiah, Sreenivas; TP, Avinash; B, Padmini Kumari (Rumah Sakit Umum Pusat (RSUP) Dr. M. Djamil, 2025)
Background: The Proximal Femoral Nail Antirotation (PFNA2) surgical implant has been developed as an efficient internal fixation device for treating intertrochanteric fractures. This study aims to evaluate the functional outcomes of geriatric patients with intertrochanteric fractures treated with the PFNA2, focusing on pain alleviation and hip function recovery. Materials and Methods: This was a single-center, observational, prospective study conducted at a tertiary care hospital. A total of 100 patients with intertrochanteric fractures were included. Patients treated with PFNA2 were followed up for 6 months. The functional outcomes were measured using the Visual Analogue Scale (VAS) for pain and the Harris Hip Score (HHS) for hip function. Results: The average age of the 100 patients was 66.47 ± 6.66 years. The majority of patients in this study had A2-type fractures, as classified by the AO/OTA system. Both the VAS for pain and the HHS for hip function showed significant improvement between the pre-operative and 6-month post-operative assessments. Conclusion: The Proximal Femoral Nail A2 is an excellent treatment option for elderly patients with intertrochanteric fractures, providing significant improvements in pain relief and functional outcomes.